2017
DOI: 10.12659/msm.901736
|View full text |Cite
|
Sign up to set email alerts
|

Association Between ABO Blood Type and Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Unilateral Total Hip Arthroplasty Surgery in China

Abstract: BackgroundPostoperative cognitive dysfunction (POCD) is a postoperative complication after surgery and anesthesia. Whether ABO blood types are associated with POCD in elderly patients undergoing unilateral total hip arthroplasty surgery in China is unclear.Material/MethodsFirstly, 142 elderly patients were divided into a POCD group and a non-POCD group according to the Mini Mental State Examination (MMSE) scores and ABO blood types were analyzed. Secondly, according to ABO blood type, the selected 226 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In addition, ABO antigens are expressed on the surfaces of a variety of cells and tissues, including red blood cells, platelets, sensory neurons, epithelial cells, and vascular endothelial cells, as well as on some plasma proteins such as vWF. Thus, ABO blood types are reportedly associated with venous thrombosis as well as various conditions such as cancer, preeclampsia, cognitive dysfunction, metabolic diseases, and infectious disorders [ 21 , 30 , 31 , 32 , 33 , 34 , 35 ]. From a different perspective, the ABO gene locus has been shown to influence angiotensin-converting enzyme activity [ 36 , 37 ]; this association suggests a potential relationship between blood type and the risk of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ABO antigens are expressed on the surfaces of a variety of cells and tissues, including red blood cells, platelets, sensory neurons, epithelial cells, and vascular endothelial cells, as well as on some plasma proteins such as vWF. Thus, ABO blood types are reportedly associated with venous thrombosis as well as various conditions such as cancer, preeclampsia, cognitive dysfunction, metabolic diseases, and infectious disorders [ 21 , 30 , 31 , 32 , 33 , 34 , 35 ]. From a different perspective, the ABO gene locus has been shown to influence angiotensin-converting enzyme activity [ 36 , 37 ]; this association suggests a potential relationship between blood type and the risk of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The Numerical Rating Scale (NRS) was used to evaluate the subjective sleep quality of patients in the night prior to and following surgery (0 points for the best sleep, 10 points for the worst sleep) (21). The visual analogue scale (VAS) (29) was used to evaluate the pain intensity during rest and the movement on the first and the third postoperative days.…”
Section: Primary Outcomementioning
confidence: 99%
“…At present, the clinical assessment of postoperative cognitive dysfunction (POCD) is the MMSE, [14][15][16] Montreal cognitive assessment (MoCA) 17 and Wechsler Memory Scale (WMS). 16 Li et al 14 used MMSE on the relationship between ABO blood type and POCD in elderly patients undergoing unilateral total hip replacement. Han et al 15 confirmed that early POCD after tonsillectomy in children could be assessed using the MMSE.…”
Section: Discussionmentioning
confidence: 99%